Bell-shaped extraction device assisted liquid-liquid microextraction technique and its optimization using response-surface methodology - Čabala, Radomír; Bursová, Miroslava (Journal of chromatography. A, 2012)
We have developed a new microextraction technique for equilibrium, non-exhaustive analyte preconcentration from aqueous solutions into organic solvents lighter than water. The key point of the method is application of specially designed and optimized bell-shaped extraction device, BSED. The technique has been tested and applied to the preconcentration of selected volatile and semi volatile compounds which were determined by gas chromatography/mass spectrometry in spiked water samples. The significant parameters of the extraction have been found using chemometric procedures and these parameters were optimized using the central composite design (CCD) for two solvents. The analyte preconcentration factors were in a range from 8.3 to 161.8 (repeatability from 7 to 14%) for heptane, and 50.0-105.0 (repeatability from 0 to 5%) for tert-butyl acetate. The reproducibility of the technique was within 1-8%. The values of limits of detection and determination were 0.1-3.3 ng mL(-1) for heptane and 0.3-10.7 ng mL(-1) for tert-butyl acetate. The new microextraction technique has been found to be a cheap, simple and flexible alternative to the common procedures, such as SPME or LLME. This BSED-LLME technique can also be combined with other separation methods, e.g., HPLC or CE.
Keywords: Reproducibility of Results; chemické látky znečišťující vodu; voda; Gas Chromatography-Mass Spectrometry; plynová chromatografie s hmotnostně spektrometrickou detekcí; Water Pollutants, Chemical; Liquid Phase Microextraction; pitná voda; Mineral Waters; mikroextrakce kapalné fáze; Drinking Water; Water; minerální vody; reprodukovatelnost výsledků; Equipment Design; design vybavení